1986
DOI: 10.3354/meps031015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in a benthic community associated with dense beds of a burrowing deposit feeder, Callianassa californiensis

Abstract: Various functional group hypotheses have provided different prehctions for the influence of mobile deposit feeders on the composition of marine soft-sediment communities. Two that have received particular attenhon are the trophic group amensalism and mobhty mode hypotheses. Trophic group amensalism suggests that deposit feeders will primarily affect suspension feeders through resuspension of sediments while a rnobhty mode approach suggests that sediment disruption is the mechanism of interaction, with sedentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(77 citation statements)
references
References 16 publications
4
72
0
1
Order By: Relevance
“…Experimental evidence to support this has been provided from both field-and laboratory-based studies, which have demonstrated strong links between individual bioturbating species and their associated communities (e.g. Posey 1986, Warwick et al 1986, 1990, Posey et al 1991, Widdicombe et al 2000. Whilst the primary effects of trawling, such as the direct mortality of species due to damage from the fishing gear, has been well studied (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Experimental evidence to support this has been provided from both field-and laboratory-based studies, which have demonstrated strong links between individual bioturbating species and their associated communities (e.g. Posey 1986, Warwick et al 1986, 1990, Posey et al 1991, Widdicombe et al 2000. Whilst the primary effects of trawling, such as the direct mortality of species due to damage from the fishing gear, has been well studied (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Already Posey (1986) and Thrush (1988), finding the exclusion of the same feeding modes, reject the apphcabihty of trophic group amensalism. Trophic group amensalism means that one trophic group (deposit-feeders, inhibitors) exclude another trophic group and epifaunal sessiles (suspension-feeders, amensals).…”
Section: Trophic Group Responsementioning
confidence: 99%
“…Predatory crabs and polychaetes, grazing snails and amphipods as well as suspension-feeding barnacles and polychaetes were found on the mussels, in their algal cover, on sponges or in shell debris entangled in byssus threads. Tsuchiya & Nishihira (1985, 1986) studied the community of experimental mussel patches on rocky substrates and found diverse feeding habits associated with them.…”
Section: Epifaunal Distribution Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioturbators modify physical as well as chemical characteristics of the sediment (e.g., Bertness, 1985;Levinton, 1989;Reise, 2002) and thus can affect other organisms sharing this habitat in various ways (Brenchley, 1981;Posey, 1986Posey, , 1987Posey et al, 1991). Large burrowing organisms such as shrimps, crabs and polychaetes are of particular significance, especially if they occur at high densities and/or construct extensive semi-permanent galleries (e.g., Peterson, 1977;Montague, 1980;Brenchley, 1981;Hoffman et al, 1984;Bertness, 1985;Brey, 1991).…”
Section: Introductionmentioning
confidence: 99%